Power rating and tools wear in milling of hardened SAE 4340 steel with minimum quantity of fluid (MQF) - Callisaya, Emanuele Schneider [UNESP] (2017)
Currently, many industries are seeking to lower the use of lubricating fluids in machining processes without losing the quality of the workpieces, as an affordable alternative arises the possibility to applicate the minimal quantity of fluid (MQF) technique. This study is focused on interpretation and evaluation of hardened SAE 4340 steel milling process using the MQF at different flow rates compared to conventional lubrication. With the implementation of a data acquisition system to measure the milling dynamic, it was possible to know all the present variations on the power rating during the process. After the tests, an appropriate statistical analysis of results was applied in order to better understand the effects of the MQF and correlate the output variables. Moreover, this project allows us to have an applicable vision of cutting process costs and study an important industrial material. As a result, the measurement and validation of the use of MQF in tangential and frontal milling process of hardened steels show good correlation with the dimension of carbide cutters wears and influence on the level of power rating, as it is detailed in this paper.